Cytotoxic Effect of Jati Belanda Leaves towards Cancer Cell Lines - Muhammad Da'i (Indonesian Journal of Cancer Chemoprevention, 2015)
The initial research of Jati Belanda leaves extract (JBE) showed the inhibition of breast cancer cell growth (T47D). The phytochemistry screening showed that JBE contain flavonoid, alkaloid, polifenol, and volatile oil. The development of anticancer drugs need the molecular mechanism investigation in order to produce cancer-targeted drugs. The objective of this research is to determine the molecular mechanism of JBE cytotoxicity effect towards cancer cell lines. This research began with cytotoxicity asssay in vitro of JBE towards some cancer cell lines by MTT method. JBE was given in some variety of concentration. The result of this study showed that JBE do not contain tirosid, and contain flavonoid in the concentration of 0,976%. The result of cytotoxicity assay towards MCF-7, HeLa, T47D and Vero showed IC50 value 36,50; 58,02; 53,36; 1806,22 dan 2451,65 µg/mL respectively. It is concluded that JBE have a strong potency to inhibit the growth of WiDr cancer cell line.Keywords : jati belanda, T47D cells, cytotoxicity